Effect of breastfeeding on children's health and its relationship to NRAMP1 expression: A cross-sectional study. (November 2021) - Fatimah,; Massi, Muhammad Nasrum; Febriani, A. Dwi Bahagia; Hatta, Mochammad; Permatasari, Tria Astika Endah; Hidayati, Elli; Hamidah,; Khumaidi, Mohammad Adib; Akaputra, Risky; Turrahmi, Hirfa; Anggraini, Rinda Putri
Abstract: Toddlers with exclusive breastfeeding can increase immunity in preventing infectious diseases such as Upper Respiratory Tract Infections (ARI). The body's resistance to disease is controlled by Natural Resistance-Associated Macrophage Protein 1 (NRAMP1). NRAMP1 contributes to the pathophysiology of several intercellular infections, including ARI. The purpose of this study was to determine the effect of breastfeeding on children's health and its relationship to NRAMP1 expression. A cross-sectional study was conducted on 124 toddlers in October 2020–June 2021. Toddlers were selected purposively from three Community Health Centers in Central Jakarta. The first group (n = 62) was exclusive breastfeeding and the second group (n = 62) was not exclusive breastfeeding. The characteristics of mothers and toddlers were collected using a structured questionnaire supported by medical record data. Meanwhile, NRAMP1 expression and NRAMP1 protein levels were obtained from the examination of blood samples. Examination of NRAMP1 gene mRNA expression by real-time PCR method and serum NRAMP1 protein levels by ELISA method. Data were analyzed using t-test, ANOVA, and multiple linear regression. The results obtained that the average mRNA expression of NRAMP1 gene and protein levels of NRAMP1 in infants who were not exclusive breastfeeding were 6.88 fold change (FC) and 315.02 pg/ml compared to those who received exclusive breastfeeding of 11.36 FC and 1087.74 pg./ml. Parity, immunization history, exclusive breastfeeding, and frequency of ARI were significantly associated with NRAMP1 gene mRNA expression and NRAMP1 protein levels (P < 0.05). Maternal and under-five age, gender, and nutritional status were not significantly related (P > 0.05). Exclusive breastfeeding was the dominant factor influencing NRAMP1 gene mRNA expression (OR: 4268) and NRAMP1 protein content (OR: 737, 362). Antibodies obtained from exclusive breastfeeding in synergy with the NRAMP1 gene form the body's immunity in infants suffering from ARI. Highlights: Breast milk contains antibodies that work in synergy with the NRAMP1 gene mRNA expression and NRAMP1 protein levels to form body immunity in children with ARI. Exclusive breastfeeding significantly increased the NRAMP1 gene mRNA expression and NRAMP1 protein levels. Immunization can significantly increase NRAMP1 gene mRNA expression and NRAMP1 protein levels. Exclusive breastfeeding can increase NRAMP1 gene mRNA expression, and NRAMP1 protein levels improved children's health.